Kesiapsiagaan Masyarakat Kota Cilegon dalam Menghadapi Bencana Gempa Bumi dan Tsunami - Maulida, Lisa; Ocktadinata, Robbi; Adhayanti, Baety (citeus, 2022)
Disaster preparedness is an important matter, especially for people living in disaster-prone areas. Cilegon City has a high risk of earthquake and tsunami disasters. The purpose of this study was to determine the level of community preparedness in the city of Cilegon in facing the earthquake and tsunami disasters. This research is a descriptive study with a cross-sectional approach. The sampling technique used was cluster sampling in the Kelurahan so that five Kelurahan were selected. One hundred respondents from five Kelurahan were taken consecutively. The data collection technique uses the LIPI-Unesco 2006 questionnaire, which consists of 38 statement items of five parameters: knowledge, attitudes towards disaster risks, policies and guidelines, plans for disaster emergencies, disaster warning systems, and the ability to mobilize resources. The data were analyzed descriptively by determining the percentage based on the ready, not ready, and unprepared categories. The research results found that respondents with the ready category were 29 percent, 56 percent less ready, 15 percent not ready. This study concludes that most respondents fall less prepared to face earthquake and tsunami disasters. This result should get the government and other related parties' attention for the safety of the community.